Osteoglycin silencing exerts inhibitory effects on myocardial fibrosis and epithelial/endothelial‐mesenchymal transformation in a mouse model of myocarditis. (3rd November 2020) - Fang, Yan; Chang, Zhitang; Xu, Zhicheng; Hu, Jing; Zhou, Haiwen; Yu, Songping; Wan, Xuan
Abstract: Osteoglycin (Ogn), a class III SLRP member with multiple glycosylation sites, has been proposed to be engaged in cardiac dysfunction and adverse remodeling in human heart failure following myocardial infarction. However, the underlying mechanism remains to be elucidated. Thus, we sought to define the role of Ogn in regulation of the Wnt pathway on myocardial fibrosis and epithelial/endothelial‐mesenchymal transformation (EMT/EndMT) in mice with myocarditis. The pathological changes are observed, while hematoxylin–eosin staining and picric acid Sirius red staining were conducted in successfully constructed myocarditis mouse models. Immunohistochemistry and enzyme‐linked immunosorbent assay were adopted to determine Ogn and β‐catenin levels and serum procollagen propeptide concentrations in the mouse myocardial tissues, respectively. Expression of Ogn and Wnt signaling pathway‐related factors were measured by reverse transcription quantitative polymerase chain reaction and western blot assay, cell viability by 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, and cell cycle distribution and apoptosis by flow cytometry. We saw indicative pathological changes accompanied by many Ogn and β‐catenin positive cells and increased serum procollagen propeptide, in the mouse myocardial tissues. Loss function assays showed reduced levels of Ogn, β‐catenin, LRP6, TGF‐β1, Twist, FSP‐1, α‐SMA and higher levels of E‐cadherin and VE‐cadherin, together with decreased proliferation rate, as well as increased apoptosis rate, indicating that the Wnt signaling pathway, proliferation were inhibited while apoptosis was enhanced with upon gene silencing. Coherently, depletion of Ogn inhibits myocardial fibroblasts proliferation and EMT/EndMT while facilitating myocardial fibroblasts apoptosis in myocarditis through the Wnt signaling pathway, thus serving as an intervention target for the molecular treatment of myocarditis.